The relationship of body image with symptoms of depression and anxiety in patients with anorexia nervosa during outpatient psychotherapy: results of the ANTOP study - Junne, Florian; Wild, Beate; Friederich, Hans-Christoph; Herzog, Wolfgang (Psychotherapy, 2016)
Body image disturbance represents a central characteristic of anorexia nervosa (AN). Depression and anxiety are the most common mental comorbidities in patients with AN. This study aims to investigate the relationship of body image with symptoms of depression and anxiety during outpatient psychotherapy in AN. Analyses were conducted using the data set of the Anorexia Nervosa Treatment Outpatient Study (ANTOP) randomized controlled trial. The ANTOP study included N = 242 females with AN between 18 and 56 years of age. The trial was designed to compare enhanced cognitive behavioral therapy (CBT-E) and focal psychodynamic therapy (FPT) with optimized treatment as usual (TAU-O) for patients with AN. The analyses on body image dimensions were conducted using measures of correlations and multiple linear regression analyses to assess the relationship and longitudinal prediction of symptoms of depression and anxiety by body image dimensions. Results showed that body image perceptions were significantly associated with symptoms of depression and anxiety in patients with AN at all treatment stages. In addition, body image dimensions at early treatment stages predict depression and anxiety in follow-up measurements. The correlation of symptoms of depression and anxiety by body image perceptions increased along treatment course. The persistence of body image disturbance, while body mass index increases under treatment (persistency effect), may constitute a relevant factor contributing to the course of the most common affective comorbidities of depression and anxiety in patients with AN. Body image disturbances in patients with AN should therefore be explicitly targeted within the specialized psychotherapy of affected patients. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Gesehen am 05.04.2019